Barriers to creativity among IIUM undergraduate students - Hilal , Huda Mohammad Hassan (s.n, 2012)
This study aims to identify the barriers to creativity as experienced by undergraduate students. In addition, it also assesses the severity of these barriers to male and female groups. The findings revealed that barriers related to task achievement are the most critical barriers to creativity and there is a significant difference between male and female groups in relation to the level of difficulty in encountering creativity barriers.